The impact of retirement on age related cognitive decline – a systematic review - Meng, Annette (BMC Geriatr, 2017)
BACKGROUND: Knowledge on factors affecting the rate of cognitive decline and how to maintain cognitive functioning in old age becomes increasingly relevant. The purpose of the current study was to systematically review the evidence for the impact of retirement on cognitive functioning and on age related cognitive decline. METHOD: We conducted a systematic literature review, following the principles of the PRISMA statement, of longitudinal studies on the association between retirement and cognition. RESULTS: Only seven studies fulfilled the inclusion criteria. We found weak evidence that retirement accelerates the rate of cognitive decline in crystallised abilities, but only for individuals retiring from jobs high in complexity with people. The evidence of the impact of retirement on the rate of decline in fluid cognitive abilities is conflicting. CONCLUSION: The review revealed a major knowledge gap in regards to the impact of retirement on cognitive decline. More knowledge on the association between retirement and age related cognitive decline as well as knowledge on the mechanisms behind these associations is needed. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/s12877-017-0556-7) contains supplementary material, which is available to authorized users.